Mergers, Aggregate Productivity, and Markups - Peter Chen (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2019)
I study the aggregate impact of mergers on productivity and markups growth for a sample of 16 European economies. Instrumented with staggered antitrust policy changes and predetermined firm-size distributions, a three-percentage-point increase in an industry's merger rate causes a one-percentage-point increase in annual productivity growth. The effect on an industry's markups growth is statistically indistinguishable from zero. I use deal-level data to explore the firm-level mechanism. Relative to peer firms, an acquired firm experiences faster Hicks-neutral productivity growth and rising market share, suggesting the quantitatively important channel is scale economies. Markups growth is also higher among acquired firms, but the impact is offset in the aggregate by decreases in peer-firm markups growth.
Keywords: 330